Pengembangan Produk Minyak Nilam Dalam Upaya Memenuhi Standar Quality Patchouli Alcohol Menggunakan Chemometric - Zikrul Khalid Zikrul Khalid (Jurnal Serambi Engineering, 2017)
Patchouli oil is one of the largest export commodity in Indonesia, But today quality of patchouli oil is still very low it is characterized by low content of patchoulialkohol as the main component. This study aims to analyze the main component of patchouli oil (patchoulialkohol) quickly without damaging the sample. The design of this study using the model calibration and validation of patchouli alcohol by using Partial Least Square (PLS) as part of the analysis Chemometrics. The results showed that the improved performance in the pretreatment PLS performance multiplicative scatter correction with RPD greatest value is 302.5. So it can be classified into good performance model of the correlation coefficient (r) is high 0.99, the coefficient of determination (R2) a good 83%, and an error value (RMSECV) the smallest is 0.02.